(untitled) (Asian Journal of Social Science Studies, 2019)
Background: It has been observed that some Nigerian Families that immigrated to North America (NINA) seem to have very stressful marital relationships that lead to separation or divorce. The goal of this study was to determine the level of marital satisfaction among NINA Method: A simple, standardized survey tool was utilized to measure the index of marital satisfaction (IMS). The score varied from 0-100 with a lower score (<30 points) indicating marital satisfaction. A demographic questionnaire was also administered to the subjects. Descriptive data analysis and level of marital satisfaction were computed in SPSS (version 25). Results: Forty-five of the fifty questionnaires were returned completed. Fifty-one percent of respondents were female. The majority (44%) were between the ages of 41-50 years. 81% were married and living with spouses. Average year of marriage was 13.5 years. The majority (85%) of respondents were married in Nigeria with only one spouse immigrating first (35%). The primary reason for immigration was employment for most subjects (48%). Seventy-two percent of the respondents scored < 30 on the IMS scale, indicating marital satisfaction. The scores were not significant when compared within the demographic variable groups. Most participants (71.4%) reported significant marital satisfaction (Z=-3.209, p=0.001. r = 0.47). Conclusion: Initial pilot study did not support the observation in the Nigeria community regarding stressful marital relationships among NINA. The IMS tool may not be sensitive to the Nigerian marriage culture and possible factors affecting marital satisfaction with cultural influence. The authors plan to conduct a more extensive study with a qualitative approach to elicit the Nigerian culturally sensitive factors.